Online identification of process systems in the frequency domain. (2nd September 2011) - Wang, Ya-Gang; Xu, Xiao-Ming; Cai, Wen-Jian
In this paper, a new online identification technique for single-input single-output processes in the frequency domain is proposed. The method can identify multiple points on process frequency response over the important frequency range of interest. Consequently, an accurate transfer function can be obtained directly by matching the model in the frequency domain. The application on closed-loop test has been employed to show both effectiveness and practicality of the method.